1979
DOI: 10.1002/bit.260210709
|View full text |Cite
|
Sign up to set email alerts
|

Algal single cell protein from wastewater treatment and renovation process

Abstract: SummaryA source of high-quality protein for animal feed. based upon algae recovered in the process of upgrading waste oxidation pond effluents and promising to be particularly economical. is being developed at the Technion. Unlike other types of single cell protein (SCP), the algal protein does not have to return the full production cost but only that of concentration and final processing. The balance is shared by the value of waste disposal and the reclaimed water. Whereas such systems as activated sludge req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

1980
1980
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 4 publications
0
19
0
2
Order By: Relevance
“…Up to the late 1970s no polyelectrolyte flocculant effective for micro-algal effluent was available (Moraine et al 1979), but effective polyelectrolytes were later found (Shelef et al 1984a). Cationic polyelectrolytes are now considered as the most effective flocculants for the recovery of microalgae (Uduman et al 2010).…”
Section: Flocculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to the late 1970s no polyelectrolyte flocculant effective for micro-algal effluent was available (Moraine et al 1979), but effective polyelectrolytes were later found (Shelef et al 1984a). Cationic polyelectrolytes are now considered as the most effective flocculants for the recovery of microalgae (Uduman et al 2010).…”
Section: Flocculationmentioning
confidence: 99%
“…Flocculation and froth flotation has been found to be effective in the removal of micro-algae from wastewater using fine air bubbles (no dimensions given) generated by a sparger with gas pressure of 3 atmospheres (Moraine et al 1979). …”
Section: Flotationmentioning
confidence: 99%
See 1 more Smart Citation
“…However from a practical point of view, the depth should be greater than 20 cm (i.e. 40-50 cm) to allow for the sludge layer and for maintaining the needed HRT (Moraine et al 1979). …”
Section: Depthmentioning
confidence: 99%
“…Achieving an energy return based on the production of biodiesel alone is extremely challenging, however, with 50% of studies on microalgal biodiesel reporting an EORI of <1 [10][11][12][13]. Anaerobic digestion of wet microalgae is potentially an energetically more favourable option as it utilises the entire biomass and does not require drying before digestion [9,[14][15][16] One of the major challenges in achieving an energy return from the production of biofuel from microalgae is harvesting and concentrating the algae [3,17,18]; this is due to a number of factors including the dilute nature of the algal suspension at 0.02%-0.05% dry solids [19,20]; the small size of micro-algal cells (most algae are below 30 µm) [21]; the similarity in density of the algal cells to that of the growth medium [22]; and the negative surface charge on the algae that results in dispersed stable algal suspensions [23][24][25].…”
Section: Introductionmentioning
confidence: 99%